Research progress on neuromolecular imaging of REM sleep behavior disorder - Geng, Chaofan; Zhang, Hongju (Frontiers in Neurology, 2022)
Idiopathic rapid eye movement sleep behavior disorder (iRBD) is an important non-motor complication of Parkinson's disease. At the same time, iRBD is considered to be the prodromal stage of α-synucleinopathy. This high risk of conversion suggests that iRBD becomes a nerve It is a window for early research on degenerative diseases and is the best candidate for neuroprotection trials. A wide range of neuroimaging techniques have improved our understanding of iRBD as a prodromal stage of the disease. In addition, neuroimaging of abnormal iRBD is expected to be a potential biomarker for predicting clinical phenotypic transformation. This article reviews the research progress of neuromolecular imaging in patients with iRBD from the perspective of iRBD transforming synucleinopathies.